Diagnostic Issues of Binge Eating in Eating Disorders. (26th February 2013) - Birgegård, Andreas; Clinton, David; Norring, Claes
Abstract: Background: Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria for eating disorders (EDs) are problematic and due to be revised. One area of debate concerns binge eating. Aims: We investigated the impact of four aspects of binge eating (binge size, loss of control, frequency of objective and subjective binge eating) assessed by questionnaire and interview in adult ED patients on concurrent and follow‐up symptoms. Method: Data came from two independent naturalistic Swedish ED databases ( N = 2354, with 12‐month follow‐up; and N = 597, with 36‐month follow‐up). Results: We found fair concurrent validity of criteria assessed using questionnaire, but poor concurrent validity for interview assessment, and no prognostic validity regardless of assessment method. Conclusions: The findings give support to some planned DSM‐5 revisions, but challenge the assumption of binge eating as a useful diagnostic criterion, as well as having implications for measurement. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.